Design and development of a film-based intervention about teenage men and unintended pregnancy: Applying the Medical Research Council framework in practice. (April 2015) - Aventin, Áine; Lohan, Maria; O'Halloran, Peter; Henderson, Marion
Highlights: Details the design and development of a sex education intervention for teenage men. Shares a model of intervention development to critique and enhance MRC guidelines. Responds to calls for gender-specific unintended pregnancy interventions. Abstract: Following the UK Medical Research Council's (MRC) guidelines for the development and evaluation of complex interventions, this study aimed to design, develop and optimise an educational intervention about young men and unintended teenage pregnancy based around an interactive film. The process involved identification of the relevant evidence base, development of a theoretical understanding of the phenomenon of unintended teenage pregnancy in relation to young men, and exploratory mixed methods research. The result was an evidence-based, theory-informed, user-endorsed intervention designed to meet the much neglected pregnancy education needs of teenage men and intended to increase both boys' and girls' intentions to avoid an unplanned pregnancy during adolescence. In prioritising the development phase, this paper addresses a gap in the literature on the processes of research-informed intervention design. It illustrates the application of the MRC guidelines in practice while offering a critique and additional guidance to programme developers on the MRC prescribed processes of developing interventions. Key lessons learned were: (1) know and engage the target population and engage gatekeepers in addressing contextual complexities; (2) know the targeted behaviours and model a process of change; and (3) look beyond development to evaluation and implementation.